A Strategy Based on Loop Analysis to Develop Peptide Epitopes: Application to SARS-CoV-2 Spike Protein - Di Vona, Maria Luisa; Rossolini, Gian Maria; Sette, Marco (Frontiers in Molecular Biosciences, 2021)
Many current strategies for inducing an immune response rely on the production of an antigenic protein. Such methods can be problematic if the folding of the antigenic protein is incorrect. To avoid this problem, we propose a method based on grafting specific regions of the chosen antigenic protein onto biocompatible polymeric matrices, so that they can mimic portions of the antigenic protein. These regions are selected following the criterion according to which they are not folded, are exposed to the solvent and are not already present in the human body, so that they are not recognized by the immune system as self. Regions are selected using the primary sequence of the protein and, where possible, its tertiary structure. The application of this strategy to the Spike protein of SARS-CoV-2 is presented.